The Bab Al-Mandab Strait And Its Strategic Importance In The Zionist War on Gaza From A Geopolitical Perspective. (Journal of the College of Basic Education, 2026)
The study aimed to reveal the geopolitical reality of the Bab al-Mandab Strait by examining the host's role in the naval blockade imposed on the Zionist entity in order to restrict its regional influence, This study emphasized the geopolitical role of the strait in this war, as it was employed in the service of the Palestinian cause, especially after the emergence of the Houthi Ansar Allah as a regional actor possessing geographical and military capabilities that qualify it to perform regional roles by imposing a naval blockade in Bab al-Mandab on the Zionist entity to stop its military campaign on the Gaza Strip. The study recommends the need to work to unify the position of Arab and Islamic countries to create a bloc against the Zionist entity, to halt its criminal practices that destabilize the security of the Middle East, and its expansionist projects aimed at establishing a Greater Israel from the Nile to the Euphrates. Remaining inactive in the face of this reality means that Arab countries will lose their lands and maritime ports, especially the Bab al-Mandab and Hormuz Straits.